2008
DOI: 10.1074/jbc.m709382200
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Regulation of Human Pregnane X Receptor by Micro-RNA Affects the Expression of Cytochrome P450 3A4

Abstract: Pregnane X receptor (PXR) is a major transcription factor regulating the inducible expression of a variety of transporters and drug-metabolizing enzymes, including CYP3A4 (cytochrome P450 3A4). We first found that the PXR mRNA level was not correlated with the PXR protein level in a panel of 25 human livers, indicating the involvement of post-transcriptional regulation. Notably, a potential miR-148a recognition element was identified in the 3-untranslated region of human PXR mRNA. We investigated whether PXR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
202
1
6

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 255 publications
(213 citation statements)
references
References 28 publications
(27 reference statements)
4
202
1
6
Order By: Relevance
“…The MIR148A gene is quite polymorphic, however, and variation in the gene region exhibits marked population differentiation representing one of the strongest signatures of selection among 117 miRNA regions tested throughout the genome (14). The levels of miR-148a expression also vary markedly across individuals (15), raising the possibility that genetic variation in the region of MIR148A may affect miR-148a expression, which may in turn affect differential HLA-C expression levels. We sequenced 7.7 kb (−6057 to +1674 relative to the distance from the mature miRNA sequence), including the MIR148A gene and flanking regions in 219 EA, identifying 26 polymorphic positions, of which 11 had a minor allele frequency of ≥5% (Fig.…”
Section: Significancementioning
confidence: 99%
“…The MIR148A gene is quite polymorphic, however, and variation in the gene region exhibits marked population differentiation representing one of the strongest signatures of selection among 117 miRNA regions tested throughout the genome (14). The levels of miR-148a expression also vary markedly across individuals (15), raising the possibility that genetic variation in the region of MIR148A may affect miR-148a expression, which may in turn affect differential HLA-C expression levels. We sequenced 7.7 kb (−6057 to +1674 relative to the distance from the mature miRNA sequence), including the MIR148A gene and flanking regions in 219 EA, identifying 26 polymorphic positions, of which 11 had a minor allele frequency of ≥5% (Fig.…”
Section: Significancementioning
confidence: 99%
“…However, the miRNA:mRNA pairs largely remain to be identified. Recently, we reported that miRNAs were involved in the regulation of human xenobiotics-metabolizing enzymes such as CYP1B1 (Tsuchiya et al, 2006) and CYP2E1 (Mohri et al, 2010) and human nuclear receptors such as pregnane X receptor (Takagi et al, 2008), vitamin D receptor (Mohri et al, 2009), and hepatocyte nuclear factor 4α (Takagi et al, 2010). As a sequel study, we focused on human aryl hydrocarbon receptor nuclear translocator (ARNT).…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrated that the miR-148a regulates PXR but not CYP3A4 (Takagi et al, 2008). Interestingly, the miR-148-dependent regulation of PXR affected the induction of endogenous CYP3A4 in human colon carcinoma-derived LS180 cells.…”
Section: Cyp3a4 and Pregnane X Receptor (Pxr)mentioning
confidence: 67%